The addition of Polyethylene-g-Maleic Anhydride as a compatibilizer on properties of low density polyethylene / water hyacinth fiber (Einchhornia Crassiper) composites - Kuppusamy, Sivalingam; Supri, A. Ghani; Siti Shuhadah (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology (MUCEET) 2009 organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis, 20th - 22nd June 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.